Strategies to aid self‐isolation and quarantine for individuals with severe and persistent mental illness during the COVID‐19 pandemic: A systematic review. Issue 4 (17th November 2021) - Bahji, Anees; Bach, Paxton; Danilewitz, Marlon; el‐Guebaly, Nady; Doty, Benjamin; Thompson, Laura; Clarke, Diana E.; Ghosh, Sumantra Monty; Crockford, David
Abstract : Background: Individuals with severe and persistent mental illness (SPMI) have a higher risk of contracting COVID‐19 than individuals without SPMI. In combination with physical distancing, hygiene protocols, and vaccines, quarantine and self‐isolation are primary means of viral containment. However, individuals with SPMI may experience more difficulties with mandated quarantine or self‐isolation because of their illness(es), stigma, and marginalization. To date, there is a lack of consensus on strategies that could aid such individuals in completing isolation. Aim: This review aimed to synthesize evidence for interventions to support self‐isolation and mandated quarantine for COVID‐19 among individuals with SPMIs. Methods: We followed the PRISMA guidelines, searching 19 electronic databases (9 published literature registries and 10 gray literature sources). We looked for relevant randomized controlled trials, quasi‐experimental studies, and program evaluations of the effectiveness of relevant psychosocial, pharmacological, harm reduction, and addiction management strategies to support isolation settings or quarantine requirements for individuals with any SPMI (e.g., any mental disorder, substance use disorder, or their combination). Findings: Of 10, 298 total records that were located, 5582 were duplicate citations. Upon screening the remaining 4716 unique records by title and abstract, we excluded a further 3562 records. Only one original article met our inclusion criteria after reviewing the full texts of the remaining 1154 citations. To support individuals experiencing homelessness during the COVID‐19 pandemic, San Francisco developed an isolation hotel that reduced COVID‐19 hospital strain for 1009 participants (25% had a mental health disorder and 26% had a substance use disorder). While 81% completed their hotel stay, 48 patients had behavioral health needs that exceeded the hotel's capabilities. No other studies met our review's eligibility criteria. Most articles located by the search simply proposed solutions or discussed the challenges brought by COVID‐19 for people with SPMIs. While some documents went a step further (e.g., shelter guidance documents to support individuals experiencing homelessness), these rarely addressed individuals with SPMIs directly. Conclusions: This systematic review evaluated evidence from published and gray literature on interventions to support self‐isolation and mandated COVID‐19 quarantine for individuals with SPMIs. Only one study met our inclusion criteria. This study found a beneficial effect of a dedicated isolation hotel for individuals experiencing homelessness and COVID‐19—where approximately 25%–50% of the study sample had a mental or substance use disorder. While there has been an abundance of COVID‐19 protocols in general, information for SPMIs is lacking. As the pandemic continues and we better prepare for future pandemics, developing protocols for supporting SPMIs in this context is imperative. Highlights: Individuals with severe and persistent mental illness (SPMI) have a higher risk of contracting COVID‐19 than individuals without SPMI. This review aimed to synthesize evidence for interventions to support self‐isolation and mandated quarantine for COVID‐19 among individuals with SPMIs. Only one study met our inclusion criteria. This study found a beneficial effect of a dedicated isolation hotel for individuals experiencing homelessness and COVID‐19—where approximately 25%–50% of the study sample had a mental or substance use disorder. While there has been an abundance of COVID‐19 protocols in general, information for SPMIs is lacking. As the pandemic continues and we better prepare for future pandemics, developing protocols for supporting SPMIs in this context is imperative.